Efektivitas Pengobatan Topikal pada Pitiriasis Versikolor - Pusung, Andreas V.; Suling, Pieter L.; Niode, Nurdjannah J. (e-CliniC, 2021)
Abstract: Pityriasis versicolor is a chronic mild superficial fungal infection of the skin due to lipophilic fungi Malassezia. It commonly affects the face, neck, abdomen, proximal extremities, axilla, groin, and genitalia. The occurrence of this disease is not influenced by sex, albeit, age influences its incidence since it is more common in adolescents and young adults.Therefore, an effective, safe, and affordable treatment should be considered. The first-line therapy for pity-riasis versicolor is topical treatment, classified into specific and non-specific antifungal agents. This study was aimed to determine the efficacy of topical treatment in pityriasis versicolor. This was a literature review study using three databases, namely PubMed, ClinicalKey, and Google Scholar and the keywords of "topical treatment AND pityriasis versicolor". The results obtained 10 literatures that fulfilled the inclusion and exclusion criteria. Theseliteratures discussed about the efficacy of topical treatment in patients with pityriasis versicolor based on clinical and mycological cure rate and the highest percentage was more than 80% in each study. In conclusion, topical treatment was effective for pityriasis versicolor. Keywords: topical treatment, pityriasis versicolor Â  Abstrak: Pitiriasis versikolor adalah penyakit jamur superfisial ringan akibat infeksi kulit kronis oleh jamur lipofilik genus Malassezia. Infeksi ini biasanya ditemukan pada wajah, leher, perut, ektremitas proksimal, aksila, lipat paha, dan genitalia. Kejadian penyakit ini tidak dipengaruhi oleh jenis kelamin, tetapi dapat dipengaruhi oleh usia, yaitu lebih banyak terjadi pada remaja dan dewasa muda. Pengobatan topikal merupakan terapi lini pertama untuk pitiriasis versikolor dan dibagi menjadi agen antijamur nonspesifik dan agen antijamur spesifik. Penelitian ini bertujuan untuk mengetahui efektivitas pengobatan topikal pada pitiriasis versikolor. Jenis penelitian ialah literature review dengan pencarian data menggunakan tiga database yaitu PubMed, ClinicalKey, dan Google Scholar. Kata kunci yang digunakan yaitu â€œtopical treatment AND pityriasis versicolorâ€.Hasil seleksi berdasarkan kriteria inklusi dan eksklusi mendapatkan 10 literatur. Kasjian literatur penelitian menunjukkan efektivitas penggunaan pengobatan topikal pada pitiriasis versikolor berdasarkan penyembuhan klinis maupun penyembuhan mikologis dengan persentase tertinggi mencapai angka >80% pada masing-masing literatur. Simpulan penelitian ini ialah pengobatan topikal pada pitiriasis versikolor terbukti efektif. Kata kunci: pengobatan topikal, pitiriasis versikolor